2022
DOI: 10.3390/s22155724
|View full text |Cite
|
Sign up to set email alerts
|

Active Ultrasonic Structural Health Monitoring Enabled by Piezoelectric Direct-Write Transducers and Edge Computing Process

Abstract: While the active ultrasonic method is an attractive structural health monitoring (SHM) technology, many practical issues such as weight of transducers and cables, energy consumption, reliability and cost of implementation are restraining its application. To overcome these challenges, an active ultrasonic SHM technology enabled by a direct-write transducer (DWT) array and edge computing process is proposed in this work. The operation feasibility of the monitoring function is demonstrated with Lamb wave excited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…These low-profile, lightweight and highly conformable piezoelectric ultrasonic transducers are known as direct-write ultrasonic transducers and have been demonstrated to be efficient for SHM, such as for detecting the presence of various defects and plastic deformation [22,23]. By combining the scalable direct-write ultrasonic transducer technology, an active ultrasonic SHM system with edge computing capability, and the methods proposed in this work, it will be possible to realize a scalable quantitative crack size monitoring over a large area [24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…These low-profile, lightweight and highly conformable piezoelectric ultrasonic transducers are known as direct-write ultrasonic transducers and have been demonstrated to be efficient for SHM, such as for detecting the presence of various defects and plastic deformation [22,23]. By combining the scalable direct-write ultrasonic transducer technology, an active ultrasonic SHM system with edge computing capability, and the methods proposed in this work, it will be possible to realize a scalable quantitative crack size monitoring over a large area [24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we reported the application of direct-write piezoelectric ultrasonic transducers (DWTs) for fatigue crack monitoring of aluminum alloy plates [ 6 ], defect detection in aluminum plates [ 7 , 8 ], plastic strain monitoring of aluminum alloy plates [ 9 ], SHM of steel pipes [ 10 , 11 ], and defect detection in carbon fiber-reinforced polymer plates [ 12 ]. These DWTs are made of poly(vinylidenefluoride-co-trifluoroethylene) [P(VDF-TrFE)] that can be fabricated in situ on the desired structure.…”
Section: Introductionmentioning
confidence: 99%
“…Structural health monitoring (SHM) is the process of sensing, collecting, and analyzing data from a structure on a regular basis to determine its condition over time [2,3,4]. Nowadays, SHM is being used in various applications such as bridges [5], pipes [6], aircraft [7], and marine structures [8] as a non-intrusive monitoring technique to facilitate condition-based preventive maintenance.…”
Section: Introductionmentioning
confidence: 99%